Measures to stop the spread of coronavirus extended (2020)
From 29 April children and teenagers will have more scope for participating in organised sports activities and play outdoors. Official matches will not be allowed. Children aged 12 and under will be allowed to play sports together outdoors under supervision. Young people aged 13 to 18 will be allowed to play sports together outdoors under supervision, but must stay 1.5 metres apart. Municipalities will make agreements on this with local sports clubs and community sports coaches. Different municipalities may opt for different approaches. Top-level athletes will be allowed to resume training sessions at dedicated training facilities if they maintain a distance of 1.5 metres from others.